PROPERTY REGISTRATION AND ENVIRONMENTAL PROTECTION IN BRAZIL: CONTRIBUTIONS TO THE IMPLEMENTATION OF THE PRINCIPLE OF THE SOCIAL FUNCTION OF PROPERTY - Bittencourt, Guiomar Rocha Pereira Magalhães; Turatti, Luciana (Seven Editora, 2026)
The Real Estate Registry emerged, in Brazil, as a way to guarantee the legal security of real estate relations and the right to property, taking as inspiration the French and German real estate registration systems. In 1988, the Federal Constitution dealt with the right to property, conditioning its exercise in the service of the social function, and this, in turn, covers the protection and defense of the environment. In other words, there must be a conditioning between the exercise of the right to property and the preservation of the environment. The combination of environmental standards with the registration principles, in turn, favors the publicity and security that are expected of legal businesses whose object is immovable. Thus, the aim of this study is to analyze the reflexes derived from the Forest Code in real estate records. The methodological procedures adopted are bibliographic and documentary research. The method was deductive and the qualitative approach. This research aims to contribute to the elucidation of practical aspects of environmental legislation applicable to the registration of Brazilian real estate, serving as a basis for further studies and consisting of a catalyst for changes in the public records area.DOI: https://doi.org/10.56238/sevened2026.008-114